PERBANDINGAN KURIKULUM SEKOLAH DASAR INDONESIA DAN VIETNAM - Juliana Margareta Sumilat; Denysa Caroles (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Primary education plays a strategic role in shaping high-quality human capital that is adaptable to global change. Indonesia and Vietnam, two rapidly developing Southeast Asian countries in the education sector, have adopted different approaches to primary education curricula, both oriented toward 21st-century learning goals. This study compares the primary school curricula of Indonesia and Vietnam, focusing on educational structure, curriculum content, pedagogical strategies, language of instruction, and implementation challenges. Using a qualitative method based on literature analysis of national policies, international reports, and academic studies, the findings show that Indonesia’s Merdeka Curriculum emphasizes flexibility, project-based learning, and character building, while Vietnam’s 2018 General Education Curriculum follows a competency-based and cross-disciplinary integration model with an outcome-based assessment system. Both countries face similar implementation issues such as regional disparities, teacher readiness, and digital learning integration. The study suggests that regional collaboration and mutual learning can contribute to improving the quality and equity of primary education in Southeast Asia.